Objectively measured physical activity is associated with parameters of bone in 70-year-old men and women - Johansson, Jonas; Nordström, Anna; Nordström, Peter (Bone (New York, N.Y.), 2015)
As the world's population ages, the occurrence of osteoporosis-related fractures is projected to increase. Low areal bone mineral density (aBMD), a well-known risk factor for fractures, may be influenced by physical activity (PA). In this cross-sectional study, we aimed to investigate potential associations between objective measures of PA and bone properties, in a population-based cohort of 1228 70-year-old men and women. We measured volumetric BMD (vBMD, mg/cm3) together with cross-sectional area (CSA, mm2) by peripheral quantitative computed tomography at sites located 4% and 66% in the distal–proximal trajectory at the tibia and radius. We also measured aBMD (g/cm2) by dual energy X-ray absorptiometry at the femoral neck, lumbar spine (L1–L4) and radius. Participants wore triaxial accelerometers for 7 consecutive days to obtain objective estimates of PA. The intensity of the objective PA was divided into light (100–1951counts/min [CPM]), moderate (1952–5724cpm) and vigorous (≥5725cpm). Maximal accelerations for the anterior–posterior (z), medio-lateral (x), and vertical (y) axes were also separately assessed. Associations were investigated using bivariate correlations and multiple linear regression, adjusted for height, weight and sex. Vigorous PA showed the strongest association with femoral neck aBMD (β=0.09, p<0.001), while both moderate and vigorous PAs were associated with cortical area and trabecular vBMD in the weight-bearing tibia (all p<0.05). Peak vertical accelerations were associated significantly with cortical area (β=0.09, p<0.001) and trabecular vBMD (β=0.09, p=0.001) of the tibia, whereas peak anterior–posterior accelerations showed no correlation with these properties. No positive association was found between objectively measured PA and bone parameters of the radius. In conclusion, vertical accelerations and moderate to vigorous PA independently predict bone properties, especially in the weight-bearing tibia, in 70-year-old men and women. •We investigated associations between objective measures of physical activity (PA) and bone properties.•The cohort consisted of approximately 1200 men and women, all 70years of age.•PA of at least moderate intensity and in vertical directions associated positively with bone parameters of tibia.•No such associations were found with the non-weight bearing radius.•Weak associations indicate that PA is likely not effective to increase bone strength in 70-year-olds.